The Lost Works of Thomas Becon. (18th December 2020) - Reimer, Jonathan
Abstract: This article attributes four lost works to the literary corpus of the English clergyman and bestselling Tudor devotional author Thomas Becon (1512–1567): The Shelde of Saluacion, An Heauenly Acte, Christen Prayers and Godly Meditacions, and The Resurreccion of the Masse . It ascribes these texts to Becon in light of three types of corroborating evidence: contemporary attribution, parallels of content, and early publication history. These four lost works not only furnish a fuller picture of his literary output, but also provide new insights into his career, rhetoric, and theology. As Becon was the most popular evangelical devotional author writing in English during the sixteenth century, this analysis of his hitherto unattributed books makes a valuable contribution to the bibliography of Tudor England, especially during the transformative years of the Henrician, Edwardine, Marian, and Elizabethan Reformations.